2021
DOI: 10.3390/ijms22105143
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylation in Axonal Guidance

Abstract: How millions of axons navigate accurately toward synaptic targets during development is a long-standing question. Over decades, multiple studies have enriched our understanding of axonal pathfinding with discoveries of guidance molecules and morphogens, their receptors, and downstream signalling mechanisms. Interestingly, classification of attractive and repulsive cues can be fluid, as single guidance cues can act as both. Similarly, guidance cues can be secreted, chemotactic cues or anchored, adhesive cues. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 103 publications
0
17
0
Order By: Relevance
“…As the N-glycans were enriched from proteins on the cell membrane, the loss of these species, specifically the sialic acid moieties, may mean the loss of intracellular interactions on the cell surface of the brain cells. Studies involving neural cell adhesion molecules (NCAMs) showed that changes in glycosylation were associated with the disruption of several NCAM-dependent neurodevelopmental processes ( 44 ). A large body of work on brain sialylation has focused primarily on polysialic acid ( 34 , 39 , 45 , 46 ); however, the large abundances of sialofucosylated species should encourage the examination of sialofucosylated NCAMs in axonal guidance.…”
Section: Discussionmentioning
confidence: 99%
“…As the N-glycans were enriched from proteins on the cell membrane, the loss of these species, specifically the sialic acid moieties, may mean the loss of intracellular interactions on the cell surface of the brain cells. Studies involving neural cell adhesion molecules (NCAMs) showed that changes in glycosylation were associated with the disruption of several NCAM-dependent neurodevelopmental processes ( 44 ). A large body of work on brain sialylation has focused primarily on polysialic acid ( 34 , 39 , 45 , 46 ); however, the large abundances of sialofucosylated species should encourage the examination of sialofucosylated NCAMs in axonal guidance.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of axon guidance, many studies have shown the bifunctionality of HS and CS as guidance cues. HS is commonly associated with permissive substrates while CS, especially 4-sulfated CS, is seen as inhibitory [40]. These actions clearly depend upon alterations in the cytoskeleton.…”
Section: Plos Onementioning
confidence: 99%
“…In terms of axon guidance, many studies have shown the bifunctionality of HS and CS as guidance cues. HS is commonly associated with permissive substrates while CS, especially 4-sulfated CS, is seen as inhibitory (36). Proteins that have been implicated in axon guidance such as Sema5A and RPTPσ have been shown to interact with both CS and HS at binding sites unique to the type of GAG chain (7, 37).…”
Section: Discussionmentioning
confidence: 99%